Environment-friendly formaldehyde-free negative oxygen ion automobile glass film and manufacturing method thereof
By using specific proportions of raw materials and preparation steps in automotive glass films, the problem that existing automotive glass films cannot continuously release negative oxygen ions and have poor environmental protection effects is solved, and efficient negative oxygen ions release and heat insulation effects are achieved. Improves the weather resistance and mechanical strength of the membrane.
Patent Information
- Application Number
- CN202411138768.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-19
AI Technical Summary
The existing automotive glass film cannot continuously release negative oxygen ions, and the environmental protection effect and the effect of benefiting human health are not good.
Adopt mixed resin emulsion, rare earth nano cerium oxide, metal nanooxide, glass fiber powder, vitrified microbeads, nano negative ion powder, dispersant, ultraviolet absorber, wetting agent, thickening agent, defoaming agent, and surfactant The environmentally friendly negative oxygen ion automotive glass film composed of agent, anti-mold agent and leveling agent improves the negative oxygen ion release and heat insulation effect through specific raw material ratios and preparation steps.
It realizes the aldehyde-free environmental protection of automotive glass film, improves the release of negative oxygen ions, enhances the insulation effect, weather resistance and mechanical strength, and has a wide range of application prospects.
Smart Images

Figure BDA0005000148380000041 
Figure BDA0005000148380000051 
Figure BDA0005000148380000061
Abstract
Description
Technical Field
[0001] The invention relates to the field of glass films, and in particular to an environmentally friendly formaldehyde-free negative oxygen ion automobile glass film. Background Art
[0002] Car glass film can not only be used to change the color of vision, but also has the effects of heat insulation, cold resistance, explosion and shock resistance. Due to the lack of air circulation in the car, the temperature in the car rises quickly, and the car glass film with heat insulation function can effectively block the transmission of heat, and the high content of negative oxygen ions in the car is beneficial to health, while the existing car glass film cannot continuously release negative oxygen ions, increase the concentration of negative oxygen ions in the car, and the environmental protection effect and the effect of car glass film on human health are not good. For this reason, we propose an environmentally friendly formaldehyde-free negative oxygen ion car glass film to solve the defects and deficiencies of the existing technology. Summary of the invention
[0003] In view of the above problems, the present invention proposes an environmentally friendly formaldehyde-free negative oxygen ion automobile glass film.
[0004] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:
[0005] An environmentally friendly formaldehyde-free negative oxygen ion automobile glass film, the glass film is made of the following raw materials in parts by weight:
[0006] 80-150 parts of mixed resin emulsion;
[0007] 1-5 parts of rare earth nano cerium oxide;
[0008] 1-3 parts of metal nano oxide;
[0009] 1-2 parts of glass fiber powder;
[0010] 1-3 parts of vitrified microbeads;
[0011] 5-10 parts of nano negative ion powder;
[0012] Dispersant 2-10 parts;
[0013] 1-4 parts of ultraviolet absorber;
[0014] Wetting agent 1-3 parts;
[0015] Thickener 1-5 parts;
[0016] 1-2 parts of defoaming agent;
[0017] 1-2 parts of surfactant;
[0018] 0.1-0.5 parts of mildew inhibitor;
[0019] Leveling agent 0.2-0.8 parts;
[0020] The mixed resin emulsion is composed of a mixture of an aqueous polyurethane resin emulsion, a cationic aqueous acrylic resin emulsion, and an aqueous acrylic modified polyurethane dispersion emulsion.
[0021] Preferably, the glass film is made of the following raw materials in parts by weight:
[0022] 60-130 parts of mixed resin emulsion;
[0023] 2-4.5 parts of rare earth nano cerium oxide;
[0024] 1.5-2.5 parts of metal nano oxide;
[0025] 1.2-1.8 parts of glass fiber powder;
[0026] 1.4-2.4 parts of vitrified microspheres;
[0027] 6.5-8.8 parts of nano negative ion powder;
[0028] Dispersant 3.6-8.2 parts;
[0029] 2.5-3.4 parts of ultraviolet absorber;
[0030] Wetting agent 1.5-2.3 parts;
[0031] Thickener 2.3-4.1 parts;
[0032] Defoaming agent 1.2-1.6 parts;
[0033] 1.2-1.6 parts of surfactant;
[0034] 0.2-0.4 parts of mildew inhibitor;
[0035] 0.4-0.6 parts of leveling agent.
[0036] Preferably, the glass film is made of the following raw materials in parts by weight:
[0037] 85 parts of mixed resin emulsion;
[0038] 3.4 parts of rare earth nano cerium oxide;
[0039] 1.9 parts of metal nano oxide;
[0040] 1.6 parts of glass fiber powder;
[0041] 2.1 parts of vitrified microspheres;
[0042] 7.3 parts of nano negative ion powder;
[0043] Dispersant 5.6 parts;
[0044] 2.8 parts of ultraviolet absorber;
[0045] Wetting agent 1.9 parts;
[0046] Thickener 3.4 parts;
[0047] 1.4 parts of defoaming agent;
[0048] 1.4 parts of surfactant;
[0049] 0.3 parts of mildew inhibitor;
[0050] 0.5 parts of leveling agent.
[0051] Preferably, the mass ratio of the aqueous polyurethane resin emulsion, the cationic aqueous acrylic resin emulsion, and the aqueous acrylic modified polyurethane dispersion emulsion is (1-4):2:1.
[0052] Preferably, the mass ratio of the aqueous polyurethane resin emulsion, the cationic aqueous acrylic resin emulsion, and the aqueous acrylic modified polyurethane dispersion emulsion is 2:2:1.
[0053] Preferably, the nano negative ion powder is nano tourmaline powder.
[0054] Preferably, the metal nano-oxide is composed of nano-titanium dioxide and nano-zinc oxide in a mass ratio of (1-2):1.
[0055] Preferably, the specific preparation steps of the automobile glass film are:
[0056] (1) stirring and dispersing an aqueous polyurethane resin emulsion, a cationic aqueous acrylic resin emulsion, and an aqueous acrylic modified polyurethane dispersion emulsion in a high-speed stirrer at 1200-1500 rpm to obtain a mixed resin emulsion;
[0057] (2) adding rare earth nano-cerium oxide, metal nano-oxide, glass fiber powder, vitrified micro-beads, nano-anion powder and dispersant, and continuously ultrasonicating for 2-3 hours at a power of 100 W to fully disperse the raw materials into the mixed resin emulsion;
[0058] (3) adding the ultraviolet absorber, wetting agent, thickener, defoamer, surfactant, mildew preventive, and leveling agent into a high-speed stirrer and mixing and dispersing for 15-20 minutes to obtain a film-forming mixed solution;
[0059] (4) Finally, the film-forming mixed liquid is coated on the surface of the automobile glass. After coating, the dispersion uniformity of the film-forming mixed liquid is enhanced by ultrasound, and it is irradiated with an ultraviolet lamp until it is cured. It is further cured at 50-65° C. to form a film, thereby obtaining a formaldehyde-free negative oxygen ion automobile glass film.
[0060] Due to the adoption of the above technical scheme, the beneficial effects of the present invention are as follows: the present invention prepares an environmentally friendly formaldehyde-free negative oxygen ion automobile glass film by preparing a mixed resin emulsion, and under a specific raw material ratio, the ultraviolet absorption rate and heat insulation effect of the automobile glass film can be effectively improved, and the negative oxygen ion release amount of the automobile glass film can be increased, thereby achieving formaldehyde-free and environmentally friendly automobile glass film. The automobile glass film of the present invention also has good weather resistance, yellowing resistance and mechanical strength, and has broad application prospects when used on automobile glass. DETAILED DESCRIPTION
[0061] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0062] Embodiment 1:
[0063] The environmentally friendly formaldehyde-free negative oxygen ion automobile glass film of this embodiment is prepared from the raw materials in parts by weight shown in the following table:
[0065]
[0067] Among them, the mass ratio of water-based polyurethane resin emulsion, cationic water-based acrylic resin emulsion and water-based acrylic modified polyurethane dispersion emulsion is 2:2:1.
[0068] Wherein, the nanometer negative ion powder is nanometer tourmaline powder.
[0069] The nano metal oxide is composed of nano titanium dioxide and nano zinc oxide in a mass ratio of 2:1.
[0070] The specific preparation steps of the automobile glass film in this embodiment are as follows:
[0071] (1) stirring and dispersing an aqueous polyurethane resin emulsion, a cationic aqueous acrylic resin emulsion, and an aqueous acrylic modified polyurethane dispersion emulsion in a high-speed stirrer at 1500 rpm to obtain a mixed resin emulsion;
[0072] (2) adding rare earth nano-cerium oxide, nano-metal oxide, glass fiber powder, vitrified microbeads, nano-anion powder and dispersant, and continuously ultrasonicating for 3 hours at a power of 100 W to fully disperse the raw materials into the mixed resin emulsion;
[0073] (3) adding the ultraviolet absorber, wetting agent, thickener, defoamer, surfactant, mildew preventive, and leveling agent into a high-speed stirrer and mixing and dispersing for 20 minutes to obtain a film-forming mixed solution;
[0074] (4) Finally, the film-forming mixed liquid is coated on the surface of the automobile glass. After coating, the dispersion uniformity of the film-forming mixed liquid is enhanced by ultrasound, and it is irradiated with an ultraviolet lamp until it is cured. Then, the film is further cured at 55° C. to obtain a formaldehyde-free negative oxygen ion automobile glass film.
[0075] Embodiment 2:
[0076] The environmentally friendly formaldehyde-free negative oxygen ion automobile glass film of this embodiment is prepared from the raw materials in parts by weight shown in the following table:
[0077]
[0078]
[0079] Among them, the mass ratio of waterborne polyurethane resin emulsion, cationic waterborne acrylic resin emulsion and waterborne acrylic modified polyurethane dispersion emulsion is 1:2:1.
[0080] Wherein, the nanometer negative ion powder is nanometer tourmaline powder.
[0081] The nano metal oxide is composed of nano titanium dioxide and nano zinc oxide in a mass ratio of 2:1.
[0082] The specific preparation steps of the automobile glass film in this embodiment are as follows:
[0083] (1) stirring and dispersing an aqueous polyurethane resin emulsion, a cationic aqueous acrylic resin emulsion, and an aqueous acrylic modified polyurethane dispersion emulsion in a high-speed stirrer at 1400 rpm to obtain a mixed resin emulsion;
[0084] (2) adding rare earth nano-cerium oxide, nano-metal oxide, glass fiber powder, vitrified microbeads, nano-anion powder and dispersant, and continuously ultrasonicating for 3 hours at a power of 100 W to fully disperse the raw materials into the mixed resin emulsion;
[0085] (3) adding the ultraviolet absorber, wetting agent, thickener, defoamer, surfactant, mildew preventive, and leveling agent into a high-speed stirrer and mixing and dispersing for 20 minutes to obtain a film-forming mixed solution;
[0086] (4) Finally, the film-forming mixed liquid is coated on the surface of the automobile glass. After coating, the dispersion uniformity of the film-forming mixed liquid is enhanced by ultrasound, and it is irradiated with an ultraviolet lamp until it is cured. The film is further cured at 60° C. to obtain a formaldehyde-free negative oxygen ion automobile glass film.
[0087] Embodiment 3:
[0088] The environmentally friendly formaldehyde-free negative oxygen ion automobile glass film of this embodiment is prepared from the raw materials in parts by weight shown in the following table:
[0089]
[0090] Among them, the mass ratio of water-based polyurethane resin emulsion, cationic water-based acrylic resin emulsion and water-based acrylic modified polyurethane dispersion emulsion is 3:2:1.
[0091] Wherein, the nanometer negative ion powder is nanometer tourmaline powder.
[0092] The nano metal oxide is composed of nano titanium dioxide and nano zinc oxide in a mass ratio of 1:1.
[0093] The specific preparation steps of the automobile glass film in this embodiment are as follows:
[0094] (1) stirring and dispersing an aqueous polyurethane resin emulsion, a cationic aqueous acrylic resin emulsion, and an aqueous acrylic modified polyurethane dispersion emulsion in a high-speed stirrer at 1300 rpm to obtain a mixed resin emulsion;
[0095] (2) adding rare earth nano-cerium oxide, nano-metal oxide, glass fiber powder, vitrified microbeads, nano-anion powder and dispersant, and continuously ultrasonicating for 3 hours at a power of 100 W to fully disperse the raw materials into the mixed resin emulsion;
[0096] (3) adding the ultraviolet absorber, wetting agent, thickener, defoamer, surfactant, mildew preventive, and leveling agent into a high-speed stirrer and mixing and dispersing for 20 minutes to obtain a film-forming mixed solution;
[0097] (4) Finally, the film-forming mixed liquid is coated on the surface of the automobile glass. After coating, the dispersion uniformity of the film-forming mixed liquid is enhanced by ultrasound, and it is irradiated with an ultraviolet lamp until it is solidified. Then, the film is further solidified at 65° C. to obtain a formaldehyde-free negative oxygen ion automobile glass film.
[0098] Embodiment 4:
[0099] The environmentally friendly formaldehyde-free negative oxygen ion automobile glass film of this embodiment is prepared from the raw materials in parts by weight shown in the following table:
[0100]
[0101] Among them, the mass ratio of waterborne polyurethane resin emulsion, cationic waterborne acrylic resin emulsion and waterborne acrylic modified polyurethane dispersion emulsion is 4:2:1.
[0102] Wherein, the nanometer negative ion powder is nanometer tourmaline powder.
[0103] The nano metal oxide is composed of nano titanium dioxide and nano zinc oxide in a mass ratio of 1:1.
[0104] The specific preparation steps of the automobile glass film in this embodiment are as follows:
[0105] (1) stirring and dispersing an aqueous polyurethane resin emulsion, a cationic aqueous acrylic resin emulsion, and an aqueous acrylic modified polyurethane dispersion emulsion in a high-speed stirrer at 1300 rpm to obtain a mixed resin emulsion;
[0106] (2) adding rare earth nano-cerium oxide, nano-metal oxide, glass fiber powder, vitrified microbeads, nano-anion powder and dispersant, and continuously ultrasonicating for 3 hours at a power of 100 W to fully disperse the raw materials into the mixed resin emulsion;
[0107] (3) adding the ultraviolet absorber, wetting agent, thickener, defoamer, surfactant, mildew preventive, and leveling agent into a high-speed stirrer and mixing and dispersing for 20 minutes to obtain a film-forming mixed solution;
[0108] (4) Finally, the film-forming mixed liquid is coated on the surface of the automobile glass. After coating, the dispersion uniformity of the film-forming mixed liquid is enhanced by ultrasound, and it is irradiated with an ultraviolet lamp until it is solidified. Then, the film is further solidified at 50° C. to obtain a formaldehyde-free negative oxygen ion automobile glass film.
[0109] Embodiment 5:
[0110] The environmentally friendly formaldehyde-free negative oxygen ion automobile glass film of this embodiment is prepared from the raw materials in parts by weight shown in the following table:
[0111]
[0112]
[0113] Among them, the mass ratio of waterborne polyurethane resin emulsion, cationic waterborne acrylic resin emulsion and waterborne acrylic modified polyurethane dispersion emulsion is 5:4:2.
[0114] Wherein, the nanometer negative ion powder is nanometer tourmaline powder.
[0115] The nano metal oxide is composed of nano titanium dioxide and nano zinc oxide in a mass ratio of 2:1.
[0116] The specific preparation steps of the automobile glass film in this embodiment are as follows:
[0117] (1) stirring and dispersing an aqueous polyurethane resin emulsion, a cationic aqueous acrylic resin emulsion, and an aqueous acrylic modified polyurethane dispersion emulsion in a high-speed stirrer at 1400 rpm to obtain a mixed resin emulsion;
[0118] (2) adding rare earth nano-cerium oxide, nano-metal oxide, glass fiber powder, vitrified microbeads, nano-anion powder and dispersant, and continuously ultrasonicating for 3 hours at a power of 100 W to fully disperse the raw materials into the mixed resin emulsion;
[0119] (3) adding the ultraviolet absorber, wetting agent, thickener, defoamer, surfactant, mildew preventive, and leveling agent into a high-speed stirrer and mixing and dispersing for 20 minutes to obtain a film-forming mixed solution;
[0120] (4) Finally, the film-forming mixed liquid is coated on the surface of the automobile glass. After coating, the dispersion uniformity of the film-forming mixed liquid is enhanced by ultrasound, and it is irradiated with an ultraviolet lamp until it is cured. The film is further cured at 60° C. to obtain a formaldehyde-free negative oxygen ion automobile glass film.
[0121] Comparative Example 1:
[0122] The raw materials and steps for preparing the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film in this comparative example are the same as those in Example 1, except that the mass ratios of the aqueous polyurethane resin emulsion, the cationic aqueous acrylic resin emulsion, and the aqueous acrylic modified polyurethane dispersion emulsion in the mixed resin emulsion are different;
[0123] Specifically: the mass ratio of water-based polyurethane resin emulsion, cationic water-based acrylic resin emulsion, and water-based acrylic modified polyurethane dispersion emulsion is 1:1:1.
[0124] Comparative Example 2:
[0125] The raw materials and steps for preparing the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film in this comparative example are the same as those in Example 1, except that the mass ratios of the aqueous polyurethane resin emulsion, the cationic aqueous acrylic resin emulsion, and the aqueous acrylic modified polyurethane dispersion emulsion in the mixed resin emulsion are different;
[0126] Specifically: the mass ratio of water-based polyurethane resin emulsion, cationic water-based acrylic resin emulsion, and water-based acrylic modified polyurethane dispersion emulsion is 1:3:1.
[0127] Comparative Example 3:
[0128] The raw materials and steps for preparing the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film in this comparative example are the same as those in Example 1, except that the mass ratios of the aqueous polyurethane resin emulsion, the cationic aqueous acrylic resin emulsion, and the aqueous acrylic modified polyurethane dispersion emulsion in the mixed resin emulsion are different;
[0129] Specifically: the mass ratio of water-based polyurethane resin emulsion, cationic water-based acrylic resin emulsion, and water-based acrylic modified polyurethane dispersion emulsion is 4:4:1.
[0130] Comparative Example 4:
[0131] The raw materials and steps for preparing the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film in this comparative example are the same as those in Example 1, except that the mass ratios of the aqueous polyurethane resin emulsion, the cationic aqueous acrylic resin emulsion, and the aqueous acrylic modified polyurethane dispersion emulsion in the mixed resin emulsion are different;
[0132] Specifically: the mass ratio of water-based polyurethane resin emulsion, cationic water-based acrylic resin emulsion, and water-based acrylic modified polyurethane dispersion emulsion is 2:2:3.
[0133] Comparative Example 5:
[0134] The raw materials and steps for preparing the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film in this comparative example are the same as those in Example 1, except that the mass ratios of the aqueous polyurethane resin emulsion, the cationic aqueous acrylic resin emulsion, and the aqueous acrylic modified polyurethane dispersion emulsion in the mixed resin emulsion are different;
[0135] Specifically: the mass ratio of water-based polyurethane resin emulsion, cationic water-based acrylic resin emulsion, and water-based acrylic modified polyurethane dispersion emulsion is 1:1:2.
[0136] Comparative Example 6:
[0137] The raw materials and steps for preparing the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film in this comparative example are the same as those in Example 1, except that the mass ratios of the aqueous polyurethane resin emulsion, the cationic aqueous acrylic resin emulsion, and the aqueous acrylic modified polyurethane dispersion emulsion in the mixed resin emulsion are different;
[0138] Specifically: the mass ratio of water-based polyurethane resin emulsion, cationic water-based acrylic resin emulsion, and water-based acrylic modified polyurethane dispersion emulsion is 1:4:1.
[0139] Comparative Example 7:
[0140] The raw materials and steps for preparing the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film in this comparative example are the same as those in Example 1, except that the mass ratios of the aqueous polyurethane resin emulsion, the cationic aqueous acrylic resin emulsion, and the aqueous acrylic modified polyurethane dispersion emulsion in the mixed resin emulsion are different;
[0141] Specifically: the mass ratio of water-based polyurethane resin emulsion, cationic water-based acrylic resin emulsion, and water-based acrylic modified polyurethane dispersion emulsion is 5:2:1.
[0142] Comparative Example 8:
[0143] The raw materials and steps for preparing the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film in this comparative example are the same as those in Example 1, and the only difference is the composition of the mixed resin emulsion. In this comparative example, the mixed resin emulsion is composed of a cationic aqueous acrylic resin emulsion and an aqueous acrylic modified polyurethane dispersion emulsion, and the mass ratio of the cationic aqueous acrylic resin emulsion to the aqueous acrylic modified polyurethane dispersion emulsion is 2:1.
[0144] Comparative Example 9:
[0145] The raw materials and steps for preparing the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film in this comparative example are the same as those in Example 1, and the only difference is the composition of the mixed resin emulsion. In this comparative example, the mixed resin emulsion consists of an aqueous polyurethane resin emulsion and an aqueous acrylic modified polyurethane dispersion emulsion, and the mass ratio of the aqueous polyurethane resin emulsion to the aqueous acrylic modified polyurethane dispersion emulsion is 2:1.
[0146] Comparative Example 10:
[0147] The raw materials and steps for preparing the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film in this comparative example are the same as those in Example 1, and the only difference is the composition of the mixed resin emulsion. In this comparative example, the mixed resin emulsion is composed of an aqueous polyurethane resin emulsion and a cationic aqueous acrylic resin emulsion, and the aqueous polyurethane resin emulsion and the cationic aqueous acrylic resin emulsion are 1:1.
[0148] Comparative Example 11:
[0149] The steps for preparing the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film in this comparative example are the same as those in Example 1, and the only difference is the raw material composition, specifically: there is no nano negative ion powder.
[0150] Performance Testing
[0151] 1. Adhesion:
[0152] According to GB / T9286-1998 "Determination of Adhesion of Paint Films", the film-forming mixed solution prepared in the examples and comparative examples was coated on a sample plate with a mixed resin, and the test was performed after curing. The adhesion was measured under constant temperature and humidity conditions.
[0153] Among them: divided into 0-5 levels, 0 is the best and 5 is the worst;
[0154] 2. Thermal insulation performance test:
[0155] According to GB / T2680 standard, UV-VIS-NIR spectrophotometer Lambda950 was used to test the surface of the film-forming mixed solution prepared in the examples and comparative examples after film formation, and the transmittance in the visible to infrared region was scanned in the range of 300-2300nm.
[0156] Test the heat insulation effect of automobile glass film:
[0157] According to the existing testing tools, the size of 150×150×150mm is selected first. 3 A cubic glass box with a wall thickness of 5 mm is prepared. The film-forming mixed liquid is coated on the surface of the cubic glass box in the coating method described in the installation embodiment to obtain visible light transmittance, near-infrared light transmittance, ultraviolet light absorptivity and temperature difference.
[0158] 3. Hardness test of automobile glass film surface:
[0159] The hardness of the automobile glass film surface of this embodiment and the comparative example was tested according to the testing method of GB / T6739-1996 "Film Hardness Pencil Test Method".
[0160] The specific test method is: apply the film-forming mixture on the sample, place it on a horizontal table, and fix the sample film of the coated material upward. Then hold the pencil at about 45 degrees, and push it on the coating surface without breaking the pencil lead. Push it about 1 cm in front of the tester at a uniform speed of about 1 cm / s, and scratch the coating surface. After each scratch, the tip of the pencil lead should be re-grinded. Repeat the scratching five times with the same hardness number of the pencil. The situation of coating scratching: in the five scratching tests, if two or more scratches are considered not to scratch the bottom plate or bottom coating of the sample, then use the pencil of the previous hardness number to perform the same test until the pencil with two or more scratches is found, and the hardness number after this pencil hardness number is recorded.
[0161] 4. Detection of negative oxygen ion release from automobile glass film:
[0162] The film-forming mixture is evenly coated on a 3cm×3cm square automobile glass sample, irradiated with an ultraviolet lamp until solidified, and further solidified into a film at 50-65°C. The square automobile glass sample coated with the film-forming mixture is then placed in a sealed chamber filled with a mixture of heated saturated air and water vapor. The temperature in the sealed chamber is controlled to 30°C. At a relative humidity of 95%, the glass film of the automobile glass sample releases negative oxygen ions in the sealed chamber. Finally, the amount of negative oxygen ions in the sealed chamber is measured.
[0163] Statistics:
[0164] Table: 1
[0165]
[0166] Table: 2
[0167]
[0168]
[0169] Based on the above, we can conclude that:
[0170] (1) The specific gravity of the mixed resin emulsion raw materials is adjusted, so that the automotive glass film has higher strength, wear resistance and yellowing resistance. When the specific gravity of the epoxy resin emulsion is increased or decreased, the final film hardness of the glass film increases or decreases accordingly.
[0171] (2) When the content of cationic water-based acrylic resin emulsion is reduced, the adhesion of the film-forming mixture on the automobile glass can be improved;
[0172] (3) When the mass ratio of the aqueous acrylic modified polyurethane dispersion emulsion is increased, the nano-anion powder is more dispersed in its resin skeleton, so that the nano-anion powder as a whole has a larger surface area to contact the outside world, further increasing the amount of negative oxygen ions released by the automobile glass film.
[0173] Table: 3
[0174]
[0175]
[0176] Table: 4
[0177]
[0178] Based on the above, we can conclude that:
[0179] (1) When the mass ratio of cationic waterborne acrylic resin emulsion increases, the near-infrared transmittance of the automotive glass film decreases, reaching a minimum of 28.65%;
[0180] (2) When the mass ratio of water-based acrylic modified polyurethane dispersion emulsion is increased, the ultraviolet absorption rate and temperature difference of the automobile glass film also increase.
[0181] 5. Test the automobile glass film prepared in this embodiment:
[0182] The testing method is based on the standards of GB18582-2008 "Limits of Harmful Substances in Interior Wall Paints for Interior Decoration and Decoration Materials" and JG / T24-2000 "Synthetic Resin Emulsion Sand Wall Architectural Paints";
[0183]
[0184]
[0185] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An environmentally friendly formaldehyde-free negative oxygen ion automobile glass film and its manufacturing method, It is characterized in that The glass film is made of the following raw materials in parts by weight: 80-150 parts of mixed resin emulsion; 1-5 parts of rare earth nano cerium oxide; 1-3 parts of nano metal oxide; 1-2 parts of glass fiber powder; 1-3 parts of vitrified microbeads; 5-10 parts of nano negative ion powder; Dispersant 2-10 parts; 1-4 parts of ultraviolet absorber; Wetting agent 1-3 parts; Thickener 1-5 parts; 1-2 parts of defoaming agent; 1-2 parts of surfactant; 0.1-0.5 parts of mildew inhibitor; Leveling agent 0.2-0.8 parts; The mixed resin emulsion is composed of a mixture of an aqueous polyurethane resin emulsion, a cationic aqueous acrylic resin emulsion, and an aqueous acrylic modified polyurethane dispersion emulsion.
2. The environmentally friendly formaldehyde-free negative oxygen ion automobile glass film according to claim 1, It is characterized in that The glass film is made of the following raw materials in parts by weight: 60-130 parts of mixed resin emulsion; 2-4.5 parts of rare earth nano cerium oxide; 1.5-2.5 parts of nano metal oxide; 1.2-1.8 parts of glass fiber powder; 1.4-2.4 parts of vitrified microspheres; 6.5-8.8 parts of nano negative ion powder; Dispersant 3.6-8.2 parts; 2.5-3.4 parts of ultraviolet absorber; Wetting agent 1.5-2.3 parts; Thickener 2.3-4.1 parts; Defoaming agent 1.2-1.6 parts; 1.2-1.6 parts of surfactant; 0.2-0.4 parts of mildew inhibitor; 0.4-0.6 parts of leveling agent.
3. The environmentally friendly formaldehyde-free negative oxygen ion automobile glass film according to claim 1, It is characterized in that The glass film is made of the following raw materials in parts by weight: 85 parts of mixed resin emulsion; 3.4 parts of rare earth nano cerium oxide; 1.9 parts of nano metal oxide; 1.6 parts of glass fiber powder; 2.1 parts of vitrified microspheres; 7.3 parts of nano negative ion powder; Dispersant 5.6 parts; 2.8 parts of ultraviolet absorber; Wetting agent 1.9 parts; Thickener 3.4 parts; 1.4 parts of defoaming agent; 1.4 parts of surfactant; 0.3 parts of mildew inhibitor; 0.5 parts of leveling agent.
4. The environmentally friendly formaldehyde-free negative oxygen ion automobile glass film according to claim 1, It is characterized in that The mass ratio of the aqueous polyurethane resin emulsion, the cationic aqueous acrylic resin emulsion and the aqueous acrylic modified polyurethane dispersion emulsion is (1-4): 2:
1.
5. The environmentally friendly formaldehyde-free negative oxygen ion automobile glass film according to claim 4, It is characterized in that The mass ratio of the aqueous polyurethane resin emulsion, the cationic aqueous acrylic resin emulsion and the aqueous acrylic modified polyurethane dispersion emulsion is 2:2:
1.
6. The environmentally friendly formaldehyde-free negative oxygen ion automobile glass film according to claim 1, It is characterized in that The nanometer negative ion powder is nanometer tourmaline powder.
7. The environmentally friendly formaldehyde-free negative oxygen ion automobile glass film according to claim 1, It is characterized in that The nano metal oxide is composed of nano titanium dioxide and nano zinc oxide in a mass ratio of (1-2):
1.
8. The method of using the environmentally friendly formaldehyde-free negative oxygen ion automobile glass film according to any one of claims 1 to 7, It is characterized in that The specific preparation steps of the automobile glass film are as follows: (1) stirring and dispersing an aqueous polyurethane resin emulsion, a cationic aqueous acrylic resin emulsion, and an aqueous acrylic modified polyurethane dispersion emulsion in a high-speed stirrer at 1200-1500 rpm to obtain a mixed resin emulsion; (2) adding rare earth nano-cerium oxide, nano-metal oxide, glass fiber powder, vitrified microbeads, nano-anion powder and dispersant, and continuously ultrasonicating for 2-3 hours at a power of 100 W to fully disperse the raw materials into the mixed resin emulsion; (3) adding the ultraviolet absorber, wetting agent, thickener, defoamer, surfactant, mildew preventive, and leveling agent into a high-speed stirrer and mixing and dispersing for 15-20 minutes to obtain a film-forming mixed solution; (4) Finally, the film-forming mixed liquid is coated on the surface of the automobile glass. After coating, the dispersion uniformity of the film-forming mixed liquid is enhanced by ultrasound, and it is irradiated with an ultraviolet lamp until it is cured. It is further cured at 50-65° C. to form a film, thereby obtaining a formaldehyde-free negative oxygen ion automobile glass film.
Citation Information
Patent Citations
Nano antibacterial water woodenware paint and preparing method thereof
CN101016431A
Composition of insulating mold coating in use for glass, and preparation method
CN101050065A
Energy-saving heat-insulating environment-protection coating material for glass and producing method thereof
CN101172778A
Polyurethane modified acrylate composite thermal-insulation energy-saving paint and preparation method thereof
CN107880754A
Low-VOC (volatile organic compound) antimicrobial art coating and preparation method thereof
CN115820092A
Cited By
Environment-friendly heat-insulating automobile paint surface protective film and preparation method thereof
CN121403808A
An environment-friendly heat-insulating automobile paint surface protection film and a preparation method thereof
CN121403808B
